MEG REVEALS SPEECH PROCESSING DELAY IN PROGRESSIVE NON FLUENT APHASIA. Issue 12 (15th November 2016) - Cope, Thomas; Sohoglu, Ediz; Patterson, Karalyn; Dawson, Catherine; Grube, Manon; Sedley, William; Davis, Matt; Rowe, James
Abstract : Progressive non fluent aphasia (PNFA) is an adult-onset neurodegenerative aphasia characterised by apraxia of speech and/or agrammatism. It is a frontotemporal dementia in which brain volume loss is subtle, and concentrated in left inferior frontal lobe. In healthy individuals, activity in this area plays a role in predictive mechanisms that integrate auditory information with prior expectations during speech perception. Patients with PNFA complain that perceiving speech is effortful. By recording concurrent electroencephalography (EEG) and magnetoencephalography (MEG) from 10 patients and 10 controls during a speech perception task, we reveal here a neural basis for this symptom. Behavioural data modelling suggests that patients make abnormally precise predictions, and have higher perceptual thresholds than controls. They display the same pattern of suppression of induced oscillatory neural activity at low-mid frequencies, but this effect is significantly delayed and extended. These results imply a 'double-hit' of impaired bottom-up perceptual processing, and top-down predictive mechanisms, explaining this frequently reported but poorly understood symptom in PNFA. These results provide the inspiration for my clinical research training fellowship, generously funded by the Association of British Neurologists and Patrick Berthoud Trust, in which I shall further study the physiology of dementia using MEG and 7Tesla MRI.